2014
DOI: 10.5152/tpd.2014.3517
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Demodex mites at the College Students Living in Dormitories in the City of Ordu

Abstract: ÖZETAmaç: Demodex folliculorum ve Demodex brevis yerleştikleri bölgelerde çeşitli semptomlar verebilmektedirler. Parazitin toplu yaşam yerlerinde görülme yüzdesinin artış gösterebileceği ile ilgili kaynak bilgiler bulunmaktadır. Bu doğrultuda çalışmada yurtlarda kalan üniversite öğrencilerinde demodex türlerinin prevelansının belirlenmesi amaçlanmıştır. Yöntemler: Araştırmanın evrenini Ordu merkezde yurtlarda kalan 300 erkek ve kadın üniversite öğrencileri oluşturmuştur. Örneklem seçiminde rastgele örnekleme y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
1
9
0
6
Order By: Relevance
“…Although Demodex mites can be found in the skin of healthy persons without creating any pathogenic effect, they could become opportunistic pathogens if the immune system of the host is suppressed . The prevalence of Demodex mites in healthy controls in other studies, which were conducted in Turkey, varied between 7 and 74.7%, while the mite density varied between 0.97/cm 2 and 2.86/cm 2 . In several studies conducted abroad, the prevalence of Demodex mites in healthy individuals was similar to those in this study, lower, or higher, while the mite density was lower than in this study .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although Demodex mites can be found in the skin of healthy persons without creating any pathogenic effect, they could become opportunistic pathogens if the immune system of the host is suppressed . The prevalence of Demodex mites in healthy controls in other studies, which were conducted in Turkey, varied between 7 and 74.7%, while the mite density varied between 0.97/cm 2 and 2.86/cm 2 . In several studies conducted abroad, the prevalence of Demodex mites in healthy individuals was similar to those in this study, lower, or higher, while the mite density was lower than in this study .…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, more men were infested with Demodex mites than women, though the differences were not significant. While some studies also showed that Demodex prevalence is higher in men than women, in other studies the prevalence was higher in women or equal among men and women …”
Section: Discussionmentioning
confidence: 87%
“…Türkiye'de yapılan çalışmalarda Demodex spp. pozitifliği ve pozitifliğine etki eden faktörler farklı gruplarda değerlendirilmiştir (1,(5)(6)(7)(8)(9)(10)(11). Gençlerde ergenlik döneminde akne vulgaris en sık rastlanılan deri problemlerinden biridir.…”
Section: Introductionunclassified
“…Demodex -type A and type B-, the most serious non-neoplastic dermatological disease [ 2 , 3 ], is not so widely known in human pathology [ 4 ]. This ascaris provokes discomfort and pain, the severity of which depends on the extent and seriousness of the disease [ 2 – 4 ], as well as on the pain proneness evidenced in third hyperalgesia test we proved several years ago [ 5 ]. Thus, pain proneness and pain redundancy might be present in both migraine sufferers and in their relatives.…”
Section: Introductionmentioning
confidence: 99%